2021
DOI: 10.3390/microorganisms9061169
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi’s Sarcoma-Associated Herpesvirus ORF7 Is Essential for Virus Production

Abstract: Kaposi’s sarcoma-associated herpesvirus (KSHV) causes Kaposi’s sarcoma, primary effusion lymphoma (PEL), and multicentric Castleman disease. Although capsid formation and maturation in the alpha-herpesvirus herpes simplex virus 1 are well understood, these processes in KSHV remain unknown. The KSHV ORF7, encoding the viral terminase (DNA cleavage and packaging protein), is thought to contribute to capsid formation; however, functional information is lacking. Here, we investigated the role of ORF7 during KSHV l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…Since the machinery for viral genome cleavage and packaging into capsids by the viral terminase does not exist in the host cells, this machinery may be a promising target for the development of antiviral drugs with high virus specificity. We have previously reported that KSHV ORF7, ORF29, and ORF67.5 form a tripartite complex, in which ORF7 functions as a center hub molecule (26). Similarly, HSV-1 UL15 (KSHV ORF29 homolog), UL28 (KSHV ORF7 homolog), and UL33 (KSHV ORF67.5 homolog) form a tripartite complex, and hexameric ring of this tripartite complex becomes an HSV-1 terminase (22).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since the machinery for viral genome cleavage and packaging into capsids by the viral terminase does not exist in the host cells, this machinery may be a promising target for the development of antiviral drugs with high virus specificity. We have previously reported that KSHV ORF7, ORF29, and ORF67.5 form a tripartite complex, in which ORF7 functions as a center hub molecule (26). Similarly, HSV-1 UL15 (KSHV ORF29 homolog), UL28 (KSHV ORF7 homolog), and UL33 (KSHV ORF67.5 homolog) form a tripartite complex, and hexameric ring of this tripartite complex becomes an HSV-1 terminase (22).…”
Section: Discussionmentioning
confidence: 99%
“…WT-BAC16 was a kind gift from Jae U. Jung and Dr. Kevin Brulois. ORF7-fsKO-BAC16, ORF7-stKO-BAC16, ORF7-fsKO Rev-BAC16, and ORF7-stKO Rev-BAC16 were previously constructed (26, 42). The transfected cells were selected under 1 mg/mL of hygromycin B (Wako, Osaka, Japan) to establish Dox-inducible recombinant KSHV-producing cell lines (WT-iSLK, ORF7-fsKO-iSLK, ORF7-stKO-iSLK, ORF7-fsKO Rev-iSLK, and ORF7-stKO Rev-iSLK, ORF7&17-DKO-iSLK, and ORF7 mC1H1-iSLK).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations